The Influence of Compensation, Work Environment and Motivation on Job Satisfaction at Medan Art Work: Inggris - Syaputra, Dadang; Telaumbanua, Faudunasokhi; Gobal, Raju (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the influence of compensation, work environment, and motivation on employee job satisfaction at Medan Art Work. This creative industry enterprise relies heavily on employee performance and innovation. The research employed a quantitative approach using a causal associative design. The population consisted of 118 employees, all of whom were selected as the research sample using a saturated sampling technique. Data were collected through a structured questionnaire utilizing a five-point Likert scale and analyzed using the SPSS statistical software to perform multiple linear regression. The findings revealed that compensation, work environment, and motivation each have a positive and significant effect on job satisfaction, both simultaneously and partially. The results highlight that financial rewards, a supportive physical and social work setting, and psychological drive are crucial components in enhancing job satisfaction in the creative sector. These findings support motivational theories, such as Herzberg’s Two-Factor Theory, the Job Characteristics Model, and Self-Determination Theory. The study contributes to the theoretical understanding of job satisfaction in creative work environments and provides practical insights for human resource policies. Organizations in similar industries are encouraged to adopt integrated strategies that enhance employee satisfaction by aligning compensation, workplace conditions, and motivational programs.